KAJIAN EKSTRAK ETANOL MAHKOTA BUNGA KETEPENG CINA (Cassia alata L) SEBAGAI BIOINDIKATOR ASAM BASA - Khairunnisa Khairunnisa; Khairuddin Khairuddin; Dwi Juli Puspitasari (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
The acid-base bioindicator is an alternative substitute for the synthetic indicator. The study about ethanol extract of Ketepeng Cina crown flowers as an acid-base bioindicator source has been done. The research about utilization of ethanol extract of Ketepeng Cina crown flower was aimed to study compound group, pH range and acid-base titration which is suitable as bioindicator. This research was performed with gradual extraction by maceration method with three solvents. The results showed that ethanol extract from Ketepeng Cina crown flowers contained flavonoid, polyphenol, alkaloid, and tannin. Extract of Ketepeng Cina crown flower was yellow in acid and orange in the base with the pH range of 7-9.Keywords: Ketepeng Cina, Bioindicator, Acid-Base, Titration.